Omnidirectional wind piezoelectric energy harvesting. (8th June 2023) - Zhang, Lanbin; He, Yixiang; Meng, Bo; Dai, Huliang; Abdelkefi, Abdessattar; Wang, Lin
Abstract: A novel energy harvester based on vortex-induced vibration of the sphere and piezoelectric effect is proposed to efficiently gather wind energy from all horizontal directions. An elastically-supported foam sphere is vertically arranged and considerably oscillates in the cross-flow direction when the wind speed is in the lock-in region. A piezoelectric beam is attached to the supported sphere by a spring and deforms periodically around the original buckling state, thereby converting kinetic energy into electrical energy. Experimental studies are performed to assess the power output of the harvester when exposed to wind flows with varying directions and speeds. The omnidirectional wind flow is divided to 12 orientations with the interval angle of 30°, and the wind speeds range from 1.17 m s −1 to 7.87 m s −1 . The testing findings indicate that the harvester has excellent consistency in both lock-in region and average power for various wind azimuths. When the wind direction is changed from 0° to 360°, the peak average power changes from 179.8 μ W to 247.5 μ W, and the wind speed region where the sphere undergoes vibration changes from 2.58 m s −1 ∼ 7.05 m s −1 to 2.58 m s −1 ∼ 7.87 m s −1 . Following that, the effects of the length of the supporting spring and the diameter of the sphere on the output average power and lock-in region are investigated experimentally. Finally, a demonstration of powering a wireless sensing node is performed to show applications of the designed energy harvester in windy conditions.